Penerapan Sistem Digital untuk Meningkatkan Efektivitas Keuangan BUMDes di Desa Ibru - Vika Indah Rahayu; Ardhiyan Saputra; Zakiah Zakiah; Siti Kurniasih; Yulismi Yulismi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: his community service program aimed to enhance the effectiveness and efficiency of financial administration at BUMDes “Suka Makmur” through digital financial reporting. The partner BUMDes still used manual bookkeeping, causing slow processes, frequent errors, and non-compliance with the PDTT Decree No. 136/2022. Traditional marketing also limited product reach. Methodology: The implementation method consisted of several stages: (1) socialization of the importance of financial digitalization; (2) training on the use of a simple accounting application tailored to BUMDes needs; (3) intensive mentoring in preparing digital financial reports; and (4) digital marketing training through e-commerce platforms and social media. Evaluation was carried out through observation, interviews, and assessment of participants’ reports. Results: The program improved administrators’ ability to prepare standardized digital financial reports and utilize digital tools for marketing. It also enhanced transparency, accountability, and trust from the community and local government. Conclusions: The community service activity conducted at BUMDes Suka Makmur, Ibru Village, has successfully enhanced the capacity of BUMDes managers in digital-based financial management and digital marketing. Limitations: The short duration, implementation in only one BUMDes, limited facilities, and participants’ varying digital literacy constrained the optimal application of the digital system and limited long-term impact assessment. Contributions: This program offers a practical model for digital transformation in rural development and contributes to agribusiness, development economics, and accounting information systems through improved digital financial and marketing competencies of BUMDes managers.